Case Report: Diagnosis of Primary Cutaneous Amyloidosis Using Dermoscopy and Reflectance Confocal Microscopy - Wang, Xiuli; Wang, Hui; Zhong, Zhenyu; Zheng, Liyun; Wang, Yifan; Guo, Ze; Li, Hui; Gao, Min (Frontiers in Medicine, 2021)
The dermoscopy and reflectance confocal microscopy (RCM) can provide new insights for diagnosis disease as non-invasive and easy-to-use tool. We observed two patients of primary cutaneous amyloidosis (PCA) by using dermoscopy and RCM respectively. The dermoscopy characteristics are as follows: brownish macules with brown or white centers surrounded by hyperpigmented blotches. And a whitish scar-like center encircled by irregular brownish hyperpigmented spots or patches. The RCM features were increased melanin deposition in the basal layer, highly refractive structures with various shapes in the enlarged papillary dermis, and the ring structure of the dermal papilla had increased pleomorphism. This is the first report on combining dermoscopy with RCM to observe PCA. We hope the characteristic dermoscopy and RCM features would provide a basis for doctors to diagnose and intervene earlier.